Oscilometria de impulso na avaliação da função pulmonar de crianças e adolescentes asmáticos - Lima, Jales Henrique Pereira De [UNIFESP] (2019)
Introduction: Asthma is one of the most common chronic diseases of childhood. Its classification can be given according to frequency, intensity of symptoms and pulmonary function. Spirometry is the traditional test for pulmonary function assessment, whereas impulse oscillometry is an alternative and easy to perform tool that measures airway impedance and assists in detecting changes in lung function. Spirometry has some limitations in asthmatic children and adolescents, often requiring complementary or substitute techniques. Objective: To evaluate and describe the pulmonary function of asthmatic children and adolescents evaluated by impulse oscillometry and compare the findings with those obtained by spirometry. Methods: A cross-sectional study evaluating the pulmonary function of 130 asthmatic children and adolescents aged 6 to 18 years, divided by disease control level according to Asthma Control Test or Children Asthma Control Test in controlled (ACT/C-ACT>19; n=70) and uncontrolled subjects (ACT/C-ACT≤19; n=60). The children and adolescents who participated in the study are assisted by the Allergy and Immunology outpatient clinic of Pediatrics Department, UNIFESP-EPM. Pulmonary function tests were performed using the MasterScreenTM equipment (CareFusion, USA). Results: One hundred thirty asthmatic children and adolescents were evaluated (51% male). The medians and interquartile range of resistance values at 5 Hz (R5%), resistance at 20 Hz (R20%), reactance at 5 Hz (X5%) and resonant frequency (Fres) were, respectively: 112,4% (86,8% – 130,2%), 105,9% (88,3% – 117,8%), 109,2% (86,4% – 160%) and 23,3 Hz (17,4 Hz – 26,2 Hz). Altered oscillometry was observed in 20% of cases and spirometry in 48%. Changes in oscillometry were more frequent in patients with controlled asthma. R5%, X5% and Fres presented moderate correlation with the main spirometric parameters, being stronger between R5% and FEF25-75% (r: -0,45; p<0,05) in the studied patients, X5% and FEV1/FVC% (r: -0,58; p<0,05) in patients with controlled asthma and between R5% and FEV1% (r: -0,39; p<0,05) in patients with uncontrolled asthma. Patients with controlled asthma who had hospitalization for asthma exacerbation had lower pulmonary function values and higher bronchodilator response values on spirometry. Patients with controlled asthma who presented bronchodilator response on oscillometry and spirometry presented higher values of R20% and Fres. Patients with uncontrolled asthma who presented bronchodilator response on spirometry had higher values of X5%. Conclusions: Impulse oscillometry values showed a moderate correlation with spirometric values. Spirometry showed greater sensitivity in the assessment of pulmonary function in asthmatic children and adolescents.